96.8k views
0 votes
when directed to solve a quadratic equation by completing the square, Sam arrived at the equation (x-(5/2))^2= (13/4). which equation could have been the original equation given to Sam?

User Nazli
by
7.5k points

1 Answer

3 votes
We have the following expression:
(x- (5/2)) ^ 2 = (13/4)
Let's rewrite the given expression:
x ^ 2 - 5x + 25/4 = (13/4)
x ^ 2 - 5x + 25/4 - 13/4 = 0
x ^ 2 - 5x + 12/4 = 0
x ^ 2 - 5x + 3 = 0
Answer:
the original equation given to Sam could have been:
x ^ 2 - 5x + 3 = 0
User Conrad Jagger
by
6.7k points